Association Between the rs13306703 and rs8192288 Variants of the SOD3 Gene and Breast Cancer and an In Silico Analysis of the Variants’ Impact - Martha Patricia Gallegos-Arreola; Asbiel Felipe Garibaldi-Ríos; María Teresa Magaña-Torres; Luis E. Figuera; Belinda Claudia Gómez-Meda; Guillermo Moisés Zúñiga-González; Ana María Puebla-Pérez; Irving Alejandro Carrillo-Dávila; Mónica Alejandra Rosales-Reynoso; Ingrid Patricia Dávalos-Rodríguez; Jorge I. Delgado-Saucedo; Marco Uriel López-Monroy (Diseases)
Background/Objectives: This study investigated the association between the rs13306703 and rs8192288 variants of the superoxide dismutase 3 (SOD3) gene and breast cancer (BC) in the Mexican population, conducting both genetic and in silico analyses. Methods: 357 healthy women and 386 BC patients were studied using TaqMan assays, qPCR, and RFLP-PCR. Results: The TT genotype and a recessive pattern of these variants were risk factors for BC (p < 0.05). Specifically, the TT genotype of rs13306703 was associated with metastatic lymph nodes, tumor progression (III–IV), luminal A, nonresponse to chemotherapy, and ki-67 ≥ 20% with diabetes mellitus (DM). Meanwhile, the GT genotype of rs8192288 was associated with menopause, luminal A, tumor progression (III–IV), ki-67 ≥ 20%, and a positive estrogen receptor with nonresponse to chemotherapy. Additionally, the TT genotype combined with DM was identified as a BC risk factor (p < 0.05). The TT haplotype was also found to be a risk factor for BC. In silico analysis suggested that these variants might influence SOD3 regulation by affecting transcription factors and active enhancer sites. Conclusions: The rs13306703 and rs8192288 variants of the SOD3 gene were associated with an increased risk of BC and may alter SOD3 regulation through effects on transcription factors, active enhancers, and transcription start sites, with modified motifs in breast epithelium cells.